Arabic Verbal Gender Agreement Through the Lens of Krashen's Theory of Second Language Acquisition - Maulani, Hikmah; Rohanda, Rohanda; Mahmud, Mahmud; Aladdin, Ashinida (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
Arabic verbal gender agreement poses challenges for second-language learners due to its complexity. This study highlights the necessity for Arabic language programs to implement input at the appropriate level (i+1) and to foster a low-anxiety environment to enhance learner acquisition in line with Krashen's framework. The participants in this study were new students (level 1) with a background in public schools who were still categorized as beginner learners, totaling 29 students. Data collection was conducted through in-depth interviews with 29 participants regarding their experiences in learning and understanding gender agreement, as well as observations to see how the language acquisition process occurs. Then, the data was analyzed using phenomenological thematic analysis. The findings reveal that learners who received comprehensible input at an appropriate level (i+1) demonstrated more accurate responses, suggesting effective language acquisition. In contrast, learners exposed to overly complex input (i+2 or higher) struggled to process the material effectively. Affective factors, such as motivation and anxiety, were also found to influence learning outcomes. High anxiety negatively impacted fluency, while a supportive learning environment enhanced language acquisition. This study highlights the importance of aligning teaching strategies with Krashen's theory, particularly the principle of comprehensible input. It is recommended that Arabic language curricula incorporate materials that gradually increase in difficulty (i+1), ensuring input is both challenging and accessible to learners. This approach can facilitate more effective language acquisition and improve overall student outcomes in Arabic language instruction